2012
DOI: 10.1096/fj.11-201343
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin regulates adipocyte function and protects against diet‐induced insulin resistance and inflammation

Abstract: The metabolic actions of the ghrelin gene-derived peptide obestatin are still unclear. We investigated obestatin effects in vitro, on adipocyte function, and in vivo, on insulin resistance and inflammation in mice fed a high-fat diet (HFD). Obestatin effects on apoptosis, differentiation, lipolysis, and glucose uptake were determined in vitro in mouse 3T3-L1 and in human subcutaneous (hSC) and omental (hOM) adipocytes. In vivo, the influence of obestatin on glucose metabolism was assessed in mice fed an HFD fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
168
3
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(194 citation statements)
references
References 63 publications
8
168
3
15
Order By: Relevance
“…In other studies, both acylated and unacylated ghrelin prevent apoptosis in the b-cell lines HIT-T15 and INS-1E, as well as in human islets (Granata et al 2007). Similarly, obestatin prevents bcell apoptosis, preserves b-cell mass, and stimulates insulin secretion in vitro and in vivo in animals, in both normal and diabetic conditions (Egido et al 2009;Granata et al 2008Granata et al , 2012. More recently, it has been observed that obestatin promotes the generation of islet-like cell clusters with increased insulin gene expression and C-peptide secretion (Baragli et al 2013).…”
Section: Type 1 Diabetesmentioning
confidence: 85%
“…In other studies, both acylated and unacylated ghrelin prevent apoptosis in the b-cell lines HIT-T15 and INS-1E, as well as in human islets (Granata et al 2007). Similarly, obestatin prevents bcell apoptosis, preserves b-cell mass, and stimulates insulin secretion in vitro and in vivo in animals, in both normal and diabetic conditions (Egido et al 2009;Granata et al 2008Granata et al , 2012. More recently, it has been observed that obestatin promotes the generation of islet-like cell clusters with increased insulin gene expression and C-peptide secretion (Baragli et al 2013).…”
Section: Type 1 Diabetesmentioning
confidence: 85%
“…In fact, the role of GPR39, the putative receptor for obestatin 40, has been questioned by different groups 18, 47, 48, although binding sites for obestatin have been shown in different cell types 15, 29, 49, 50. Our present findings have demonstrated that the selective antagonist of ghrelin receptor (D‐Lys3)‐GHRP‐6 did not alter the antiadrenergic action of obestatin, suggesting GHS‐R1a‐independent effect of the peptide and involvement of a different receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings have demonstrated that the selective antagonist of ghrelin receptor (D‐Lys3)‐GHRP‐6 did not alter the antiadrenergic action of obestatin, suggesting GHS‐R1a‐independent effect of the peptide and involvement of a different receptor. Interestingly, we have previously shown that the glucagon‐like peptide 1 receptor (GLP‐1R) may be implicated in the physiopathological actions of obestatin in several cell types 29, 49, 51, 52. This may also be possible for cardiomyocytes and endothelial cells, which express GLP‐1R 53, although more studies are needed to clarify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these effects on feeding behavior and gastrointestinal motion have been subsequently disputed and the precise identity of its cognate receptor(s) is still a matter of debate (5), obestatin indisputably exerts a variety of effects in different cell types, including pancreatic b-cells, where it increases survival and proliferation by inhibiting apoptosis and inflammation (6,7). In line with these actions, other favorable effects of obestatin have been observed on glucose and lipid metabolism, such as increased glucose uptake and insulin sensitivity as well as inhibition of lipolysis in human adipocytes (7,8).Interestingly, in addition to its helpful metabolic properties, obestatin has been shown to provide vascular benefits in experimental models. Thus, in rat aorta and the superior mesenteric artery, Agnew et al (9) have demonstrated that obestatin favorably affects endothelial function, inducing nitric oxide (NO)-dependent relaxation via an adenylate cyclase-linked GPCR.…”
mentioning
confidence: 92%
“…Even though these effects on feeding behavior and gastrointestinal motion have been subsequently disputed and the precise identity of its cognate receptor(s) is still a matter of debate (5), obestatin indisputably exerts a variety of effects in different cell types, including pancreatic b-cells, where it increases survival and proliferation by inhibiting apoptosis and inflammation (6,7). In line with these actions, other favorable effects of obestatin have been observed on glucose and lipid metabolism, such as increased glucose uptake and insulin sensitivity as well as inhibition of lipolysis in human adipocytes (7,8).…”
mentioning
confidence: 99%